2007
DOI: 10.1007/s00705-007-0979-0
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination plays minor role in excision of unit-length viral genomes from head-to-tail direct tandem repeats of porcine circovirus during DNA replication in Escherichia coli

Abstract: In this report, we confirmed previous work that a theta-replicating bacterial plasmid containing 1.75 copies of genomic porcine circovirus (PCV) DNA in head-to-tail tandem (HTT) [a partial copy of PCV type 1 (PCV1), a complete copy of PCV type 2 (PCV2) and two origins of DNA replication (Ori)] yielded three different double-stranded DNA species when transformed into Escherichia coli: the input construct (U), the unit-length PCV1/PCV2 genome with a composite Ori lacking the plasmid vector (Q(RC)) and the remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Recombination experiments in geminiviruses [192] and circoviruses [193], have shown that this genome site is a mechanistically predisposed recombination hot-spot because of the replicational release of viral genomes from genomic concatomers ( Figure 3). When these concatomers either arise following a copy-choice mediated polymerase strand switch, or break and are rescued by host double stranded break repair pathways (i.e., by recombination dependent replication [78]), recombinants that are replicationally released will have one breakpoint at the site of the strand-switch/breakage and another at the v-ori (see Section 2.2 above).…”
Section: Replication Originsmentioning
confidence: 99%
“…Recombination experiments in geminiviruses [192] and circoviruses [193], have shown that this genome site is a mechanistically predisposed recombination hot-spot because of the replicational release of viral genomes from genomic concatomers ( Figure 3). When these concatomers either arise following a copy-choice mediated polymerase strand switch, or break and are rescued by host double stranded break repair pathways (i.e., by recombination dependent replication [78]), recombinants that are replicationally released will have one breakpoint at the site of the strand-switch/breakage and another at the v-ori (see Section 2.2 above).…”
Section: Replication Originsmentioning
confidence: 99%
“…We also report the presence of genotype PCV2a strains from 2007 onward, in a confined area. The recent reappearance of genotype PCV2a strains have been described in other countries such as Korea (Kim et al, 2009), USA (Cheung, 2007) and China (GQ359003) and may represent a shift back of genotype PCV2b to genotype PCV2a.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Furthermore, several studies presented sequence evidence for PCV2 genotype group members' recombination (18,21,26). Recombination events were observed by amplicate sequencing analysis in both major PCV2 ORFs (5,32). One may surmise that the contribution of recombination to PCV2 genomic evolution may be the critical factor in initiating PMWS in an animal's immune system already weakened by lymphopenia caused by PCV2.…”
mentioning
confidence: 99%